Bi-Reforming of Biogas for Hydrogen Production with Sulfur-Resistant Multimetallic Catalyst - Poggio Fraccari, Eduardo Arístides (2023)
A multimetallic sample, NiCeSnRh/Al2O3, was tested in methane reforming with a CH4:H2O:CO2 molar ratio equal to 3:2:1. A very stable methane conversion with the time-on-stream was achieved during 20 h. Dimethyl sulfide served as a model sulfur molecule and a sulfurized sample was also tested. This achieved slightly lower conversion with a stable performance for more than 10 h and a minor but continuous decrease of its activity, after this period. The carbon dioxide conversion was always higher than the methane conversion in agreement with the lower H2/CO ratio observed with respect to the theoretical value, 2/1, indicating the sulfur might block the active sites for H2O activation. The analysis of the used catalysts showed graphitic and disordered carbon deposits.